2011
DOI: 10.1007/s11130-011-0231-7
|View full text |Cite
|
Sign up to set email alerts
|

Grain and Tortilla Quality in Landraces and Improved Maize Grown in the Highlands of Mexico

Abstract: The maize produced in the highlands of Mexico (>2,400 masl) is generally not accepted by the flour and masa and tortilla industry. The objective of this work was to evaluate the grain quality and tortilla properties of maize landraces commonly grown in the highlands of Mexico and compare them with improved germplasm (hybrids). Germplasm analysis included 11 landraces, 32 white hybrids, and six yellow hybrids. Grain quality was analyzed for a range of physical and chemical factors, as well as for alkaline cooki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
8
2
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 18 publications
6
8
2
7
Order By: Relevance
“…This variation can be due to the effect of heterosis achieved at the selection lines. These results are similar with Vazquez et al [14].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This variation can be due to the effect of heterosis achieved at the selection lines. These results are similar with Vazquez et al [14].…”
Section: Resultssupporting
confidence: 93%
“…In Table 3, we can see that genotypes native maize (12,13,14,15,16,18), the palmitic fatty acid content was lower (12.26 g/100g) than the white hybrid maize (13.16 g/100g), which means an increase of fatty acid saturated in 1% in they, however, the stearic fatty content was higher (3.30 g/100g), than observed in the hybrid maize (2.09 g/100g). Oleic acid, native maize showed a higher average content (40.83 g/100g), since the hybrid maize was minor (34.15 g/100g), it is …”
Section: Resultsmentioning
confidence: 98%
“…However, all tortillas contained high levels of protein (10.73-12.44 g 100 g -1 ). These results are in accordance with the findings of Vázquez-Carrillo et al (2011) (Fig. 3a), who determined the protein content in tortillas processed from landraces maize (9.76-12.54 g 100 g -1 ) and in maize hybrids (8.24-11.34 g 100 g -1 ).…”
Section: Resultssupporting
confidence: 92%
“…Among all treatments, tortillas prepared with ENBESB-10% had higher a value (intensity of reddish coloration) compared with the ENF counterparts. As expected, the color of tortillas made with ENBESB-10% had higher a (reddish), as in previous reports in which pigmented maize tortillas were produced (Vázquez-Carrillo et al 2011). It has been reported that these components that contribute to color in sorghum are mainly associated with the pericarp and aleurone layer.…”
Section: Resultssupporting
confidence: 87%